A New Method to Evaluate Joint Hypermobility in Paediatric Patients with Neurodevelopmental Disorders: A Preliminary Study - Leonardo Zoccante; Marco Luigi Ciceri; Gianfranco Di Gennaro; Marco Zaffanello (Children)
Background/Objectives: Neurodevelopmental disorders (NDDs) include a wide range of conditions that develop during the formation of the central nervous system, such as autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD). Tourette syndrome (TS) is another neurodevelopmental disorder characterised by motor and vocal tics, which often co-occurs with ASD and ADHD. This study explores the feasibility of assessing joint hypermobility in children with specific neurodevelopmental conditions by measuring both ankles’ passive range of motion (pROM). Methods: This study involved children diagnosed with ASD, ADHD, and TS, aged 5 to 15 years, who were compared with a control group of healthy children. The Beighton and Brighton scores and the pROM of the left and right ankles were measured. Data were analysed using SPSS version 22.0 for Windows (IBM SPSS Statistics, Chicago, IL, USA). A total of 102 subjects participated in this study (72.52% male, with a mean age of 10.7 ± 2.2 years). The sample included 24 children with ASD, 27 with ADHD, 26 with TS, and 25 healthy controls. Results: The pROM of the right and left ankles showed a significant positive correlation with the Beighton and Brighton scores in children with NDDs (ASD, ADHD, and TS combined). A trend towards higher Beighton scores (≥6) was observed in the ADHD and TS groups, with significance found in the TS group (p = 0.013). The pROM of the right ankle was significantly higher in the ADHD (p = 0.021) and TS (p = 0.013) groups compared to the controls. Although the left ankle followed a similar trend in the TS group, the difference was not statistically significant (p = 0.066). Controlling for age, the diagnosis of ASD, ADHD, and TS does not appear to impact any of the variables examined. Conclusions: There is a trend towards a higher prevalence of individuals with elevated Beighton scores in the ADHD and TS groups, suggesting greater general flexibility or hypermobility in these patients. However, the pROM of the right ankle is significantly higher in the ADHD and TS groups, with solid evidence in the TS group. These findings were not observed in children with ASD. However, it is necessary to consider the measurements obtained in relation to the patients’ age. Finally, given that the pROM of the ankles correlates with the Beighton and Brighton scores, it could be utilised for the initial screening, monitoring, and follow-up of JH in some children with NDDs. Further investigations are required.